Mapping of Women Farmers Working on Rubber Fields from a Gender Perspective in Bangsal Village, Pampangan District, Ogan Komering Ilir Regency, South Sumatra Province - Rahmah, Erieka; Seftiandra Bermana; Dewi, Husna (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research examines the role of women in rubber land management in Bansal Village, Pampangan District, Ogun Komering Ilir Regency. When men leave the village, they are more likely to work in rubber fields, just like women. The role of women who initially worked in the domestic sphere shifted to the public sphere. The research method uses descriptive qualitative with a case study strategy. Data collection was carried out by observation, interviews and documentation. The informants consisted of five main informants, one key informant and three supporting informants. The results of this research show the involvement of women farmers in managing rubber land in the public sector, even though previously they only worked in the domestic sector. This condition occurred because husbands who initially worked on rubber plantations later left their villages to look for other jobs in order to improve the family's economy. Women participate fairly in the family economy so that they become the savior of the family economy, because the results obtained from their husband's new job are still limited to fulfilling a subsistence economy.